A new species of stauromedusa, Calvadosia festivala (Cnidaria: Staurozoa: Kishinouyeidae) from India - Baroliya, Hitisha Ishawarbhai; Kundu, Rahul; Miranda, Lucília Souza (Zootaxa, 2024)
Staurozoa is a cnidarian class represented by marine benthic animals, mainly observed in intertidal and subtidal cold waters. As one of the few exceptions, in this study we described a tropical species, Calvadosia festivala n. sp., from Dwarka, Gujarat, India. We combined the morphological description with molecular data, placing the new species into a phylogenetic context with other species of Calvadosia. Calvadosia festivala n. sp. is unique in the arrangement of white nematocyst spots and in the dark (purplish brown) lines in the nodular gonads and in manubrium. The new species is closely related to Calvadosia lewisi, Calvadosia corbini, and Calvadosia tasmaniensis, sharing the pad-like adhesive structures on the exumbrellar tips of arms, externally separated from the secondary tentacles. This is the first formal description of a staurozoan species from India, the fourth species of Staurozoa described for the Indian Ocean, and the fourth recorded in tropical waters, providing relevant data to biogeographic and diversity discussions on the group.